Isolated attosecond pulse generation using multicycle pulses directly from a laser amplifier - Gilbertson, Steve; Wu, Yi; Khan, Sabih D.; Chini, Michael; Zhao, Kun; Feng, Ximao; Chang, Zenghu (My University, 2010)
Using a generalized version of double optical gating, we produced single isolated attosecond pulses with 2-mJ, 25-fs driving lasers. Temporal characterization revealed that the 160-as pulses are accompanied with very weak pre- and postpulses. The dependence of the extreme-ultraviolet spectrum on the carrier-envelope phase of the 25-fs laser exhibited a unique 2π periodicity, indicating the robustness of the subcycle gating.